Jan Hus between time and eternity: reconsidering a medieval heretic - Fudge, Thomas A. (Lexington Books, 2016)
Priest and reformer in Prague -- Did Hus' spirituality influence women and religious practice in Bohemia? -- The sex life of Jan Hus -- The eschatological Hus in an apocalyptic age -- Martyr at Constance -- Hus on trial: seeing the accused through the eyes of his enemies -- Preaching against heretics at the Council of Constance -- Friendship and faith: the prisoner and the knight -- The other sheep: reflections on heresy by a suspected heretic -- Legacy to the world -- A curious absence: Jan Hus in the Hussite crusade -- Hus in genealogies of heresy and alternative models of apostolic succession -- The seven last words of Jan Hus -- Politicizing the legend of Jan Hus: problems and perspectives -- Jan Chlum in correspondence from the Council of Constance